An automatic cough counting method and system construction for portable devices - Wang, Yixuan; Yang, Kehaoyu; Xu, Shaofeng; Rui, Shuwang; Xie, Jiaxing; Wang, Juncheng; Wang, Xin (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Cough is a common symptom of respiratory diseases, and prolonged monitoring of cough can help assist doctors in making judgments about patients’ conditions, among which cough frequency is an indicator that characterizes the state of the patient’s lungs. Therefore, the aim of this paper is to design an automatic cough counting system to monitor the number of coughs per minute for a long period of time. Methods In this paper, a complete cough counting process is proposed, including denoising, segment extraction, eigenvalue calculation, recognition, and counting process; and a wearable automatic cough counting device containing acquisition and reception software. The design and construction of the algorithm is based on realistically captured cough-containing audio from 50 patients, combined with short-time features, and Meier cepstrum coefficients as features characterizing the cough. Results The accuracy, sensitivity, specificity, and F1 score of the method were 93.24%, 97.58%, 86.97%, and 94.47%, respectively, with a Kappa value of 0.9209, an average counting error of 0.46 counts for a 60-s speech segment, and an average runtime of 2.80 ± 2.27 s. Discussion This method improves the double threshold method in terms of the threshold and eigenvalues of the cough segments’ sensitivity and has better performance in terms of accuracy, real-time performance, and computing speed, which can be applied to real-time cough counting and monitoring in small portable devices with limited computing power. The developed wearable portable automatic cough counting device and the accompanying host computer software application can realize the long-term monitoring of patients’ coughing condition.